Aplikasi Pemesanan Jasa Tour Guide Dan Vacation Planner Di Bali Berbasis Mobile - Devia Yakanita; Hendy Mahaputra; Rifky Lana Rahardian (Politeknik Negeri Cilacap, 2020)
E-Tourism is a technological innovation through e-commerce in the field of tourism. E-Tourism provides a tourism service to tourists online and the organization of tourism marketing has become more accessible. This study aims to produce a mobile-based Tour Guide and Vacation Planner booking service information system which is expected to be beneficial for tourists in planning and making their visit easier while in Bali. This application is expected to make it easier for tourists to make holiday planning in Bali so as to create an efficient and appropriate plan for tourists, and ultimately have an impact on the tourism sector in Bali. This research applies to the waterfall method. This research is based on the results of tests using interview methods and filling out questionnaires for people who play a role in tourism.